2021
DOI: 10.1017/jfm.2020.1171
|View full text |Cite
|
Sign up to set email alerts
|

2-D and 3-D measurements of flame stretch and turbulence–flame interactions in turbulent premixed flames using DNS

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 62 publications
3
23
0
Order By: Relevance
“…If h 3 is the height of A ′ above the tangent plane (see Fig. 1b), it can be shown that (Hawkes et al 2011;Veynante et al 2010;Chakraborty and Hawkes 2011;Chakraborty et al 2013;Wang et al 2021):…”
Section: Mathematical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…If h 3 is the height of A ′ above the tangent plane (see Fig. 1b), it can be shown that (Hawkes et al 2011;Veynante et al 2010;Chakraborty and Hawkes 2011;Chakraborty et al 2013;Wang et al 2021):…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…where y e1 and y e2 are distances in the principal directions �� ⃗ e 1 and �� ⃗ e 2 corresponding to principal curvatures 1 and 2 in the tangent plane at the point A . Figure 1 suggests that the measured height h 2 above the tangent t 1 in the two-dimensional plane can be expressed as (Hawkes et al 2011;Veynante et al 2010;Chakraborty and Hawkes 2011;Chakraborty et al 2013;Wang et al 2021):…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…The simulation details were given in our previous studies ,,, and are briefly introduced in this section. Three-dimensional DNS of methane/air freely propagating premixed flame with different turbulent intensities is performed.…”
Section: Dns Data Setsmentioning
confidence: 99%
“…The simulation details were given in our previous studies 29,33,34,49 and are briefly introduced in this section. Three- 1a shows a schematic of the DNS configuration.…”
Section: Dns Data Setsmentioning
confidence: 99%
“…For example, a recent study by Wang et al. (2021 b ) showed that 2-D and 3-D turbulence–flame interactions can differ qualitatively in turbulent premixed flames, with the flame normal vector being misaligned (weakly aligned) with the most extensive strain rate in 3-D (2-D) cases.…”
Section: Introductionmentioning
confidence: 99%